The Use of Urban Identity to Market Housing Projects in the Context of Urban Branding: Istanbul Case - Ince, Esma; Dincer, Iclal (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
The aim of the present study was to understand the use of urban identity elements in the marketing of housing projects in the context of Istanbul's city branding target. First, the notion of urban identity and the use of identity factors by various sectors were studied. Two topics were the focus: branding policies on an urban scale, and using identity in housing project marketing. Secondly, the conceptual background of city branding and Istanbul's branding practices were examined. Finally, as the original work of the article, the use of urban identity elements in the marketing strategy for housing projects was examined and a new classification was created. Based on a study of the marketing of housing projects, the themes of Historical/Cultural Heritage and Race Emphasis, Natural Heritage Usage, Location/Urban Network Accessibility Emphasis, and Franchising of City Name were used in the classification. Use of those themes together, called Synthesis Usage, was analyzed in depth using the purposive sample method. The investor profile, the project district, and the number of housing units were evaluated using the commercial/introductory advertising video, advertising catalogs, and the websites of 30 housing projects. It was observed that public-private partnerships and private sector actors continue to use the collective symbolic capital of the city as a marketing tool. The consumption-oriented approach and commodification of an Istanbul urban identity was critiqued.
Keywords: Use of urban identity elements; housing projects; commodification; symbolic capital; Architecture